Measuring the performance of public universities Malaysia using CCR model and ranking with Super Efficiency model - Adna, Norfarziah; Mohd Yusoff, Nazhatul Sahima; Sheikh Zolknain, Siti Sarah Alia (Academica Press Solutions, 2025)
The efficiency and productivity of a country's higher education system significantly influence its ability to develop and flourish. Furthermore, efficiency becomes a crucial performance metric for universities overall, assisting decision-makers in formulating policies that promote the intended outcomes and prudently allocating resources. There is a lot of pressure on public higher education around the world to perform better and be of higher quality. This study examines the efficiency scores of 20 public universities in Malaysia using the input-oriented CCR model and output-oriented CCR model and also the Super Efficiency model. Three inputs and five outputs are determined to measure the performance of the university. The number of postgraduate students enrolled, the number of undergraduate students enrolled, and the number of academic staff are the inputs, while the number of graduates, the number of graduates working, the number of graduates who choose to further studies, the number of graduates who choose to develop skills, and the number of graduates waiting for work placement are the outputs. The findings show that out of 20 public universities, 13 public universities are efficient with an efficiency score equal to 1 using the input-oriented CCR model and output-oriented CCR model. Meanwhile, the remaining seven public universities showed inefficient score results. UNIMAP got 4.103862 for the Super Efficiency score, which was ranked first out of thirteen efficient public universities in 2023, making it the most efficient public university. By ranking public university, interested parties, such as the higher education sector or university administration, can take steps to enhance and maximize university performance.